Tuberous root characteristics of sweet potato clones using multivariate techniques for selection of superior genotypes - Silva, Jackson da; Ferreira, Paulo Vanderlei; Oliveira, Felipe dos Santos de; Teixeira, Jadson dos Santos; Silva, Moisés Tiodoso da; Santos, Douglas Ferreira dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The objective of this study was to evaluate the tuberous root characteristics of sweet potato clones using multivariate techniques for selection of superior genotypes, the present research was carried out in the Experimental area of the Plant Genetic Breeding Sector of the Agrarian Sciences Center of the Federal University of Alagoas (SMGP/CECA/UFAL). Were evaluated 44 new clones originated from progenies of half-siblings and germanic siblings, in addition to the cultivar Sergipana Vermelha, in lines of 5 m in length, spacing 1.0 mx 0.5 m, totaling a total area of 5 m²/clone. The harvest was done at 120 days after planting the branches, in which the production of non-commercial tuberous roots (PRTNC) was evaluated, production of commercial tuberous roots (PRTC), production of tuberous roots (PTRT), total number of tuberous roots (NTRT), average weight of commercial tuberous roots (PMRTC), predominant color of tuberous root skin (CPPERT) and predominant color of the tuberosal root pulp (CPPORT). Descriptive statistics, correlation technique and principal component analysis were used. It was observed that clones 23, 36, 17 and 37 presented interesting agronomic characteristics, being recommended for the cultivation and in the analysis of main components, the variables PTRT and PRTC presented greater importance, reflecting that they discriminate the clones satisfactorily.